Classifications of Countries Basedon their Level of Development : How it is Done and How it Could Be Done - Nielsen, Lynge (IMF Working Papers; Working Paper ;, 2011)
The paper analyzes how the UNDP, the World Bank, and the IMF classify countries based on their level of development. These systems are found lacking in clarity with regard to their underlying rationale. The paper argues that a country classification system based on a transparent, data-driven methodology is preferable to one based on judgment or ad hoc rules. Such an alternative methodology is developed and used to construct classification systems using a variety of proxies for development attainment.